Protocols for bulk off-line fluid inclusion extraction for the analysis of δ13C-CH4 and δ13C-CO2 using a cavity ring-down spectroscopy (CRDS) analyser - Olivieri, Orlando Sébastien; Marassi, Valentina; Casolari, Sonia; Sissman, Olivier; Daniel, Isabelle; Fiebig, Jens; Vitale Brovarone, Alberto (Frontiers in Earth Science, 2024)
Fluid inclusions are a window into deep geological fluids, providing unique access to their nature and composition. The isotopic composition of CO2 and CH4 hosted in fluid inclusions is a powerful proxy to assess the origin and transformation of deep geological fluids, giving insights into carbon sources, fluxes, and degassing in a wide variety of geodynamic settings. Over the last 5 decades, techniques have been developed to extract fluid inclusions from their host minerals and measure their bulk composition. These techniques are often challenged by analytical artifacts including high blank levels of CO2 and CH4, fluid re-speciation, gas adsorption, and diffusion. Since these processes may alter the pristine composition of gases liberated from fluid inclusions, rigorous protocols are needed in order to evaluate the isotopic integrity of the extracted volatile species. In this study, we introduce new protocols for bulk off-line fluid inclusion extraction for the analysis of δ13C-CH4 and δ13C-CO2 using a Cavity Ring-Down Spectroscopy (CRDS) analyser (Picarro G2201-i). Two mechanical fluid extraction techniques are compared: ball milling in ZrO2 jars and sample crushing in a stainless steel sealed tube under a hydraulic press. Blanks and isotopically labelled tests with the ball milling technique suggest that rotation speed, grinding stock filling degree and filling type alter the CH4 and CO2 concentrations and isotopic compositions measured by the CRDS analyser. In contrast, the crushing technique does not generate measurable quantities of blank CH4 and CO2. The protocols presented in this study allow to extract, detect, and analyse δ13C of CH4 and CO2 for concentrations above 10 and 1,000 ppm respectively. Interlaboratory experiments allowed to replicate previously measured δ13C-CH4 values in natural fluid inclusions within 1‰ with both extraction techniques. This study highlights the potential of combining simple bulk off-line fluid inclusion extraction techniques with a CRDS analyser for δ13C analysis of CO2 and CH4 without gas separation being required.